Moderate oxidation levels of Ru nanoparticles enhance molecular oxygen activation for cross-dehydrogenative-coupling reactions via single electron transfer. Issue 53 (29th June 2017) - Lin, Mu; Dai, Lin-Xiu; Gu, Jun; Kang, Li-Qun; Wang, Yu-Hao; Si, Rui; Zhao, Ze-Qiong; Liu, Wen-Chi; Fu, Xuefeng; Sun, Ling-Dong; Zhang, Ya-Wen; Yan, Chun-Hua
Abstract : Ruthenium nanoparticles with altered surface oxidation states showed a volcano shaped relationship in molecular oxygen activation via single electron transfer for cross-dehydrogenative-coupling reactions. Abstract : For converting a homogeneous synthetic chemistry reaction to a heterogeneous one, using nanocatalysts, it is essential to investigate the underlying principles and the associated dominant factors of methodologies between inorganic nanoparticles and organic substrates. Here it is reported that novel, hydrothermally synthesized ruthenium (Ru) nanoparticles performed differently in molecular oxygen activation via single electron transfer for cross-dehydrogenative-coupling reactions, following a volcano shaped relationship between their oxidation levels and catalytic activity. Characterizations and a systematic mechanism study indicated that Ru 3+ sites contributed to more superoxo- or peroxo-like species being formed from molecular oxygen on Ru nanoparticles with a moderate oxidation level, and the Ru 3+ were the highly active species which accelerate this cross-dehydrogenative-coupling reaction via single electron transfer.